MrERF, MrbZIP, and MrSURNod of Medicago ruthenica Are Involved in Plant Growth and Abiotic Stress Response - Wu, Rina; Xu, Bo; Shi, Fengling (Frontiers in Plant Science, 2022)
Stress arising due to abiotic factors affects the plant’s growth and productivity. The outstanding performance of Medicago ruthenica in stress resistance makes it become a high quality gene resources to improve the stress tolerance of plant. Here, 3 DEGs (MrERF, MrbZIP and MrSURNod) from Medicago ruthenica, the critical role of them in stress resistance has not fully understood. Therefore, we constructed their expression vectors, then transformed them into tobacco, and subjected transgenic lines to abiotic stresses. Through a comprehensive bioinformatics, transcriptomic, morphological and physiological analysis of transgenic lines, we have revealed the critical role of them in plant growth and abiotic stress response. The up-regulation of genes can enhance the germination rate, biomass, root length and number, etc. Additionally, increase the accumulation of osmoregulation substance and activity of antioxidant enzyme. Meanwhile, they can also improve the seeds yield, increase branches, and flowering in advance thereby shorten the growth period. Maybe this is one of the ways for tobacco to cope with stress. Furthermore, the resistance of transgenic tobacco with MrERF or MrbZIP is better than that of MrSURNod. MrERF and MrbZIP can improve drought and salt tolerance of plants, while MrSURNod is beneficial to improve its drought and cold resistance. Besides, they are beneficial to root development. Notably, MrERF or MrbZIP can promote root elongation and increase root number simultaneously, while MrSURNod mainly promotes the elongation of the roots. This may be the reason why its resistance is weaker than the other two.